Uso de lambaris (astyanax sp.) Como bioindicadores de contaminação aquática no rio Vacacaí – RS, Brasil: respostas bioquímicas como ferramentas de biomonitoramento - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The aquatic ecosystems are suffering increasing contamination coming from agricultural, industrial and urban activities, compromising water quality and preservation of aquatic biota. The measurement of this contamination through biochemical biomarkers in fishes can provide reliable data to estimate sublethal effects in contaminated environments. Fish of the Astyanax sp genus were collected from three different points of the Vacacaí River of São Gabriel-RS, immediately after collection the muscle tissue was processed for determination of enzyme activities (acetylcholinesterase, catalase, glutathione S-transferase, superoxide dismutase, glutathione reductase) and levels of protein thiols (PSH) and non-protein (NPSH) by spectrophotometry. The brain tissue was processed for determination of expression levels of Nrf2, NQO-1, MT1 and GPx4. The results showed signs of environmental contamination with the induction of antioxidant defenses CAT, SOD, GST and GPX and inhibition levels of no protein thiols NPSH, GR and AchE enzyme activity and induction in Nrf2, NQO-1, GPx4 and MT1 expression. It was concluded that the parameters of oxidative stress may be important preventive and complementary tools on biomonitoring of environmental quality and preservation of aquatic ecosystems, with other classics biomarkers, helping on studies of damages to aquatic organisms.
Use of lambaris (astyanax sp.) As bioindicators of aquatic contamination in the Vacacaí river - RS, Brazil: biochemical responses as biomonitoring tools
Keywords: Marcadores bioquímicos; Ecossistemas aquáticos; Recursos naturais - Conservação; Biochemical markers; Water Ecosystems; Natural resources - Conservation; CNPQ::CIENCIAS BIOLOGICAS